DOES RELIGIOSITY MODERATE EFFECT OF PROMOTION AND FINANCIAL LITERACY ON MILENIAL INTEREST USING KPR BSI - Herdita, Khansa Putri; Zubaidi, Ahmad (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
The millennial generation represents the second-largest demographic group in Indonesia, accounting for 25.87% of the population. This study seeks to explore the factors influencing the millennial generation's interest in utilizing home financing services provided by Bank Syariah Indonesia (BSI), focusing specifically on the roles of promotion and financial literacy. Furthermore, the study investigates how religiosity moderates the relationship between these factors and millennials' interest in BSI's home financing products. The research targets millennial customers of BSI residing in South Jakarta, using a sample size of 100 respondents. The sampling method employed is non-probability purposive sampling, and data were collected through a structured questionnaire utilizing a Likert scale. For data analysis, the study adopts the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, conducted using SmartPLS 3.0 software, with a significance level set at 5%. The results demonstrate that both promotion and financial literacy have a positive and statistically significant effect on millennials' interest in using BSI's home financing services. In addition, religiosity significantly moderates the influence of these factors, further enhancing their impact on millennials' preferences and decisions regarding BSI's home financing products. These findings highlight the importance of targeted promotional strategies and improving financial literacy, as well as addressing the role of religiosity, in fostering greater interest among millennials in Islamic banking products like home financing.